دراسة تحليلية للسهوم طويلة الأمد في الجيزان الخرسانية المسلحة والجيزان المقواة بالـ FRP - غريب, محمد; وردة, ديانا (Latakia University Journal -Engineering Sciences Series, 2016)
انتشر مؤخراً استخدام صفائح الألياف البوليميرية لتقوية الجيزان الخرسانية المسلحة وذلك يعود إلى المقاومة العالية التي تعطيها صفائح التقوية مع العلم بأن وزنها قليل، إضافة الى سهولة التركيب وقلة تكاليف الصيانة في حال تم مقارنتها مع طرق التدعيم الأخرى كاستخدام الصفائح الفولاذية. كما أثبت التدعيم الخارجي باستعمال صفائح الألياف البوليميرية فعالية كبيرة في تقوية ورفع كفاءة العناصر الخرسانية المسلحة المتضررة. إلا أن دراسة تأثير السلوك الطويل الأمد للعناصر المقواة بالـ FRP لم تأخذ الحيز الكافي من الدراسة، وذلك بسبب صعوبة التنبؤ الدقيق بالسهوم طويلة الأمد وعرض الشقوق وسلوك العناصر المقواة بالـ FRP. تم في هذا البحث عرض طريقة للتنبؤ الدقيق بالسهوم في أي وقت من مرحلة الاستثمار للمنشآت الخرسانية العادية والعالية المقاومة، وفي أي عمر تحميل للخرسانة وتحت تأثير تشوهات الزحف والانكماش ومشاركة التسليح في منطقة الضغط وذلك بالنسبة للجيزان الخرسانية المسلحة، والجيزان الخرسانية المسلحة المقواة بصفائح الـ FRP. إن التنبؤ الدقيق لتزايد السهوم في العناصر الخرسانية المسلحة مع الزمن يتطلب دراسة التحليل اللاخطي للتأثيرات المتعلقة بالزمن، حيث أن هذه الدراسات عادة تستغرق زمناً طويلاً وتتطلب جهداً كبيراً[6-13]، لكن في مرحلة التصميم يمكن الاعتماد على أساليب بسيطة، تأخذ في الاعتبار العوامل الهامة التي تؤثر على تزايد السهوم مع الزمن وذلك للوصول إلى تصميم دقيق للمنشآت. ولهذا الغرض تم العمل على تطوير العديد من الأساليب المدرجة في الكودات العالمية والمحلية [1-2-3-4-14] إضافة إلى برمجة العلاقات الخاصة بالزحف والانكماش للوصول إلى طريقة تجمع بين البساطة والدقة وتقدم معلومات قيَمة عن تأثير العوامل المختلفة على السهوم المتزايدة مع الزمن. قورنت القيم التحليلية من نتائج الطريقة المقترحة مع قيم نتائج تجارب مخبرية مجراة سابقاً [8-9] وكذلك مع القيم الناتجة عن الكود الأمريكي [1] . وتبين أن القيم التحليلية توافق النتائج المخبرية بشكل جيد [8-9]. Fiber reinforced polymer (FRP) plates have gained popularity in the strengthening of reinforced concrete (RC) members due to the high strength to weight ratio, the ease of installation and low maintenance costs compared to other systems such as steel plates. Also, external bonding of fiber reinforced polymer (FRP) plate has been proven to be an effective method to strengthen and damage RC structures. However, not much attention has been given to the long-term behavioral aspects of FRP-strengthened RC members. It is difficult to accurately predict the long-term deflection, crack width and behavior of FRP-strengthened RC members. This study presents a method for predicting the deflections at any time of the service life of normal and high strength concrete structures, loaded at any age, creep coefficient and shrinkage strain and the participation of the compressive steel for RC beams, and for RC beams strengthened with FRP plates. The accurate prediction of deflections is a complex problem which requires the use of non-linear and time-dependent analytical methods. These methods are, in general, time consuming and require great effort[6-13]. However, at the design stage, simple but reliable methods which take into account the most important parameters influencing the long-term deflections may be very useful to adequately design the structure. For that purpose, many simplified methods have been developed [1-2-3-4-14]. Equations have been programmed to access the method combines the simplicity and accuracy and provides valuable information about the influence of each parameter on the increasing deflections with time. The analytical values are compared to the experimental results from some existing papers [8-9], and to the results obtained from ACI code [1]. It is found that the analytical method is in a good agreement with the experimental results from some existing papers [8-9].